TANTANGAN DAN SOLUSI DALAM MANAJEMEN PEMBIAYAAN BANK SYARIAH - Ahmad Fauzan Aflah; Juwita Silfana; Rifki Arifin Lubis; Muhammad Ikhsan Harahap (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze internal and external challenges in Islamic bank financing management and formulate strategic solutions to improve financing performance and industry competitiveness. The research method used is library research by reviewing literature, theories, empirical data, and research results related to Islamic banking. The results of the study show that the main challenges lie in the quality of human resources, operational efficiency, the risk of non-performing financing, a lack of product innovation, low Islamic financial literacy, the dominance of conventional banks, and regulatory limitations. This study also found that the application of Islamic financial technology, product diversification, regulatory strengthening, and public education are effective solutions to increase the inclusion and stability of Islamic financing.